Entrepreneurship and development - an alternative perspective - Mccullagh, C (Economic & Social Studies, 1984)
Abstract: This paper offers an alternative to the more orthodox psychological approach to the study of entrepreneurship. It suggests that an adequate theory of entrepreneurship must consider a country's political and economic history and especially the way in which this history has structured the opportunities for economic gain open to social groups in the society. It further suggests that due to the different historical experience of underdeveloped countries, and especially international monopoly capital, these opportunities will be differently structured in such societies. Whilst the particular structure may not lead to development, it will be maintained by the class structure and political system which emerges in such societies and which may resist attempts to alter that particular structure of economic opportunities. However, while such opportunities are so structured, analysis of entrepreneurship must also consider why there might be differential response to such opportunities in a society. This, it suggests, can be explained in terms of the degree of role continuity and congruity in economic roles in the society. Consideration of both the historical and the economic role level is essential for the study of entrepreneurship.
Keywords: Economics; Sociology